2015
DOI: 10.1016/j.techfore.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Alarm pendants and the technological shaping of older people's care

Abstract: Alarm pendant use among older people is often framed as one of the rational responses needed to alleviate the escalating costs of an aging population. This paper draws on qualitative data with older people and their carers to explore the effect that supplementing, and in some cases substituting, 'traditional' forms of care with this technology, has on the lives of its users. While advocates argue that alarm pendants can support independence and 'aging in place', our analysis focuses on how social relations bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 21 publications
1
29
0
2
Order By: Relevance
“…Interviews and focus groups were all audiorecorded and transcribed verbatim, typically lasting between 50 and 90 minutes. Interview and focus group transcripts were analyzed thematically and coded at a sentence to paragraph level (Pritchard & Brittain, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Interviews and focus groups were all audiorecorded and transcribed verbatim, typically lasting between 50 and 90 minutes. Interview and focus group transcripts were analyzed thematically and coded at a sentence to paragraph level (Pritchard & Brittain, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The calls are often scripted to follow a certain procedure, and the teleoperator often has no former care relationship with the care recipients; rather, he or she knows the recipient's name and about his or her care situation as a result of information on the computer screen (Garmann-Johnsen 2015). It is suggested that these kinds of check-up calls may dehumanise care situations due to the strict protocols, brief care relations (Pritchard and Brittain 2015), and limited effectiveness (Garmann-Johnsen 2015). Reservations have also been raised about the goal of using technology in eldercare to support the care recipients' independence.…”
Section: Impact On Care Relationsmentioning
confidence: 99%
“…Reservations about being dependent on modern technology and worries about power outages, unstable Internet connections, and telephone failures were raised in the literature (van Hoof et al 2011). False alarms or low reliability also evoked feelings of insecurity and unease (van Hoof et al 2011, Bouwhuis, Meesters, and Sponselee 2012) and might result in non-use (Pritchard andBrittain 2015, Hawley-Hague et al 2014). The non-use of alarm pendants has been justified by the fact that the technology fosters less autonomy and a lack of control while making older people feel disabled and stigmatised (Pritchard and Brittain 2015, Mort, Roberts, and Callén 2013, Peek et al 2014, Hawley-Hague et al 2014).…”
Section: Shift In Responsibilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Soupajärvi suggest that design of new technologies can greatly be enriched by the knowledge of the earlier experience of the users. Pritchard and Brittain (2014) explore how social relations both mediate the functioning of alarm pendants as assistive devices for the care of older persons and in turn are mediated by these devices. Alarm pendant devices are often being promoted as a convenient and cost-saving alternative to more traditional human centred care.…”
Section: Overview Of Contributionsmentioning
confidence: 99%